An Extended VIKOR Method for Interval-Valued Trapezoidal Intuitionistic Fuzzy Decision Making - S. N. Murty Kodukulla, V. Sireesha (Mathematical Statistician and Engineering Applications, 2022)
Real-world problems frequently have several non-commensurable and contradictory criteria, and there may be no solution that meets all of them at the same time. VlseKriterijumskaOptimizacija I KompromisnoResenje (VIKOR) is a technique developed to solve the decision making problems with these criteria. This paper extends themulti-criteria decision making (MCDM) technique VIKOR for interval-valued trapezoidal intuitionistic fuzzy sets (IVTrIFSs). A new ranking method based on Jaccard distance is proposed and is applied in this process. Further, the proposed IVTrIFS VIKOR is tested by applying it to solve the best green supplier problem. The results are compared with the other existing methods. The comparison study revealed that the proposed method is both effective and applicable.